What will the weather be? - DeWitt, Lynda; Croll, Carolyn (New York : HarperCollins, 1991)
Explains the basic characteristics of weather--temperature, humidity, wind speed and direction, air pressure--and how meteorologists gather data for their forecasts.
Keywords: Weather forecasting -- Juvenile literature; Weather forecasting